Analisa Determinasi TPAK di Jawa Tahun 2015-2019 - Amirull Dwi Hasti; Rian Destiningsih (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
Development is a continuous process that aims to improve the welfare of the people in an area. The economic development of a region cannot be separated from the human resources in that area. Human resources or residents in an area will act as labor, input from development or production factors, as well as the final consumer of production. This study is to see how the influence of the independent variables consisting of education, regional minimum wages, and the ratio of dependence on TPAK in the Java region in 2015-2019. The data used is secondary data with a panel of 6 provinces in Java in 2015-2019 with regression analysis by Eviews 10. The results of this study are that education and the dependency ratio have a significant positive effect, and the regional minimum wage has a negative and insignificant effect with the TPAK in the Java Region in 2015-2019. For this reason, the government is advised to determine the amount of regional minimum wages in order to realize people's welfare, it is better to pay attention to several things, namely seeing the needs of a decent life, the level of education of workers, and the number of the workforce.